СТРУКТУРНО ФУНКЦИОНАЛЬНАЯ МОДЕЛЬ ФОРМИРОВАНИЯ АКМЕЛИНГВИСТИЧЕСКОЙ КОМПЕТЕНТНОСТИ СТУДЕНТОВ МЕДИЦИНСКОГО ОБРАЗОВАНИЯ В ПРОЦЕССЕ ОБУЧЕНИЯ АНГЛИЙСКОМУ ЯЗЫКУ - Дзугаева, З.Р. (SCIENCE and SOCIETY, 2021)
This article describes a structural functional model of the formation of acmelinguistic competence of medical students in the process of teaching English. The features and specificity of the process of teaching English language to medical students are considered and a modern approach is proposed to intensify the process of developing translation skills of verb constructions.